1987
DOI: 10.1042/bj2470641
|View full text |Cite
|
Sign up to set email alerts
|

Segmental structure and protein domains in the pyruvate dehydrogenase multienzyme complex of Escherichia coli. Genetic reconstruction in vitro and 1H-n.m.r. spectroscopy

Abstract: A deletion in vitro can be made in the aceEF-lpd operon encoding the pyruvate dehydrogenase multienzyme complex of Escherichia coli, which causes deletion of two of the three homologous lipoyl domains that comprise the N-terminal half of each dihydrolipoamide acetyltransferase (E2p) polypeptide chain. An active complex is still formed and 1H-n.m.r. spectroscopy of this modified complex revealed that many of the unusually sharp resonances previously attributed to conformationally mobile segments in the wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The present studies with the genetically engineered O-lip PDH complex convincingly confirm that the innermost linker is the source of the 1.49 (1.52) ppm signals, previously assigned using trypsin-treated complexes [14], and that the EZbinding domain becomes more mobile in the absence of lipoyl domains.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present studies with the genetically engineered O-lip PDH complex convincingly confirm that the innermost linker is the source of the 1.49 (1.52) ppm signals, previously assigned using trypsin-treated complexes [14], and that the EZbinding domain becomes more mobile in the absence of lipoyl domains.…”
Section: Discussionsupporting
confidence: 88%
“…ppm derive from the methyl groups of alanine residues in the linkers associated with the lipoyl domains [14], whereas the smaller doublet at 1.49 ppm (equivalent to 1.52 ppm in [ 141) comes from the alanine residues in the innermost linker (E3-bd linker). The composite signal at 0.95 ppm has been assigned to hydrophobic residues such as leucine, isoleucine and valine, found in both the E3-binding and lipoyl domains [l 11.…”
Section: Ppm) (D) Ratio Of Lipoyl Linker Intensity To Domain Intensimentioning
confidence: 99%
“…The E3-binding domain is in turn linked by a shorter and less conspicuously (alanine+proline)-rich segment to a large (approx. 29 kDa) C-terminal, inner-core domain that houses the acetyltransferase active site and binds the Elp and other E2p chains [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…IH-NMR spectroscopy of the wild-type [10,11] and genetically engineered [6,12] PDH complexes and of appropriate synthetic peptides [13] has indicated that the (alanine + proline)-rich inter-domain segments of the E2p chains are indeed conformationally flexible. Two lipoyl domains can be deleted from the N-terminal end of the E2p chain without significant loss of catalytic activity in the resulting (pGSll0-encoded) PDH complex [14].…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal part consists of three homologous repeating sequences, forming lipoyl domains, which are separated by the apa-1 and apa-2 sequences [6,7,9]. Each lipoyl domain contains a lysyl residue as a potential covalent attachment site for a lipoyl moiety.…”
mentioning
confidence: 99%